The conventional and constitutional parameter against the criminalization of social protest and the role of the criminal judge in the protection of its legitimate exercise 2021 - Sotomayor Saavedra, Luis Enrique (2023)
The general objective was to determine how the conventional parameter is developed and of the criminal judge against the criminalization of social protest. The methodology used was basic, with a quantitative approach, descriptive level, non-experimental and cross-sectional design, the data collection was used by performing the documentary analysis technique through the documentary analysis guide instrument, which was duly validated by experts in the field. The results of the investigation determined that in the face of a criminal case derived from the exercise of the right to social protest, it is designed and recognized not only in our highest legal system but also by international instruments on human rights; this implies the assumption of a duty not only to submit to the jurisdiction of the IACHR but also to apply its jurisprudence, the same ones that are known as the parameters of conventionality or control of conventionality; where human rights have a protective nature and the judges who resolve cases with such connotation must protect their exercise due to the nature of the same